PERBANDINGAN HASIL BELAJAR PRODUKTIF AKUNTANSI DENGAN MODEL PEMBELAJARAN INKUIRI TERBIMBING DAN GROUP INVESTIGATION - Destamrini Destamrini; R Gunawan Sudarmanto; Eddy Purnomo (Faculty of Teacher Training and Education, University of Lampung, 2013)
The purpose of this research is to analyze (1) the difference in the learning result between the learning models and between the forms of the test, (2) the difference in the learning result between the learning models without considering the form of the test, (3) the difference in the learning result between the forms of the test without considering the learning model, (4) the difference in the average of learning result between the learning models by considering the form of the test, (5) the difference in the average of learning result between the forms of the test by considering the learning model, (6) interaction between the learning model and the forms of the test, and (7) the more effective learning between guided inquiry model and group investigation. The method applied is a quasi-experiment by providing treatment to two different classes; one class uses guided inquiry learning model and another class using group investigation, and considering the tests which are given. The design is 2 x 2 and data analysis using the two-lane variants with factorial design and analysis of effectiveness. The results showed that hipotesis in 1, 3, 5, 6, 7 and 8 all have differences learning result. The second hipotesis not yet with shape tes. Hipotesis 4 there are interactions between the learning model and the forms of the test that used, and (7) group investigations learning model is more effective when using multiple choice test while guided inquiry learning model is more effective when using description test.Keywords: guided inquiry learning, group investigation learning, form of the test.